Studi Literatur: Peran Guru Pendidikan Khusus di Sekolah Inklusi - Nissa Amalia; Farida Kurniawati (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The research was carried out to know the role played by teacher assistants in inclusive schools. The research method used for this study is a systematic review by capturing articles related to the research topic published between 2009-2019 through the electronic search engine Taylor and Francis Online. The initial search found 24 articles and then selected based on exclusive criteria, in which there were ten articles identified using thematic data analysis techniques. The results found that role of a teacher assistant is role pedagogic and non-pedagogic. Pedagogic roles include learning, giving assignments, helping students complete assignments, performing assignments, making IEP (individualized educational program), assessing and managing student behavior while non-pedagogic roles include emotional support, consulting, facilitating teachers, students, and parents. The results also show the importance of teacher assistants having competencies according to their educational background and building collaborative learning between classroom teachers and teacher assistants in the classroom. Limitations and recommendations for future research are discussed in this paper.